Validating self-reported cervical cancer screening among women leaving jails. - Shelby Webb; Patricia J Kelly; Joi Wickliffe; Kevin Ault; Megha Ramaswamy (PLoS ONE, 2019)
Background Despite women with criminal justice involvement reporting routine Papanicolaou (Pap) testing, significant disparities in cervical cancer outcomes exist when compared to women without criminal justice involvement. A possible reason for the discrepancy is that this group of women may be misreporting Pap testing. The objective of this study was to validate self-reported cervical cancer screening among women leaving jails. Methods We used three methods to validate self-reported cervical cancer screening for women recently released from jail: 1) Medical record review; 2) Semi-structured interview; 3) Pap test knowledge survey. After validating women's self-reported Pap tests with a review of their medical records, we scored interviews for Pap test recall, and used Pap test knowledge survey scores to compare scores between women who accurately reported Pap tests vs. those who did not. Results Sixty-one percent (N = 14/23) self-reported cervical cancer screenings were accurate per medical record review. Comparing participants who did and did not accurately self-report a Pap test, we found a significant difference in Pap test recall scores (1.90 vs. 0.00, t = 3.87, p < .01) and Pap test knowledge scores (13.50 vs. 12.13, t = 2.42, p < .05). Conclusion Self-report of cervical cancer screening was more likely to be accurate if a woman's Pap test knowledge was high. Clinicians might take extra care in describing screening and distinguishing between Pap tests and pelvic exams to support the cervical health of women with lower knowledge.